Pengaruh media pembelajaran vidio animasi terhadap hasil belajar IPA siswa di kelas VI SD - Nurul Rahmi Azura; Azri Ranuwaldy Sugma; Mustafa Habib (Didaktika Dwija Indria, 2025)
The aim of this research is to determine the effect of using animated video learning media on student learning outcomes in science learning about the solar system in class VI elementary school. Animated video is a learning medium which includes images, writing and audio which can help teachers in conveying learning. This research uses a quasi-experimental method with a pretest-posttest control group design. The subject of the research carried out by this researcher was class VI elementary school consisting of 30 students who were divided into two classes, the first class was called the control class and the second was the experimental class. In the initial stage, pretest questions were given in each class, after that learning was carried out using animated videos in the experimental class and in the control class using normal learning. After learning is complete, posttest questions are given to each class to determine the students' final knowledge. The pretest and posttest results were analyzed using the t-test after fulfilling the homogeneity and normality tests. It can be concluded that the use of animated video learning media can improve student learning outcomes in the solar system material.